Conflito de interesses em pesquisa clínica e integridade : aportes à luz da teoria do reconhecimento de Axel Honneth - Cassimiro, Márcia de Cássia (2018)
This thesis investigates, based on Axel Honneth's Theory of Recognition, Conflicts of Interest (COIs) and integrity in the process of emancipation and management of a diversity of borderline issues such as: disrespect (Mißachtung) and violation (Verletzung) to the citizen, capable of provoking profound transformations and changes to society in the face of the peculiar characteristics of a concrete social reality of participatory democratic domain. Issues of integrity, disrespect for patients, research participants, society, and institutions are discussed; as well as issues related to injustice and dishonesty. COIs and misconduct provoke political, technical, ethical, and moral offenses when individuals are violated in nonrecognition dynamics. The three patterns (affective, juridical, solidarity) can result in: (i) psychic death in the first pattern of recognition (affective); (ii) social death in the second (legal) pattern; and (iii) social humiliation in the third pattern (solidarity). The struggle for recognition is the condition for conflicts to be normative. There are models of justice such as: redistributive; economicist, and of recognition. But the research is delimited around the contribution of recognition to the theoretical confrontation of COIs and integrity. It is presumed that the struggle for recognition is a fundamental element to instantiate research on COIs and integrity, thus articulating an interdisciplinary approach (Philosophy and Health). The title — contains elements that articulated in a certain way, indicate what I intend to discuss in a multidisciplinary way in this research: the investigation into the contributions of the Theory of Recognition applied to the dilemmas of COIs and integrity. Chapter 1. Conflict of interests (COIs) in health and integrity — aims to: (a) explain about COIs and integrity at the level of citizens' basic needs and the opposition of interests between private and public actors to explain the citizen's struggle for sustainability of your demands; and (b) expound on COIs and integrity in an interdisciplinary way, that is, transversely articulating the philosophical point of view and the health sciences so that citizens can be recognized. The following subchapters make up the first part: 1.1. Methodological strategy; 1.2. COIs and integrity: how they are managed; 1.3. COI typology and policy diversity, and 1.4. Bioethics: synoptic overview and reflections. Chapter 2. Axel Honneth's Theory of Recognition (RT) — addresses Honneth's RT, focusing on the following subchapters: 2.1. Social conflicts and normativity; 2.2. From self-preservation to recognition: normative resizing of conflicts; 2.3. Normative recognition standards, and 2.4. Denial of normative standards of recognition. Chapter 3. Contributions of Honneth's TR to the thesis — articulates Honneth's RT with elements present in the health sciences, thus aiming to raise debate and justify the importance of defending the application of Honneth's RT to the movement fighting for right to quality policies for all. To do so, I make a conceptual inflection on COIs, integrity and scientific policies, and as a result of these interrelationships, I present some solutions for the researched dilemmas, focusing on the following subchapters: 3.1. Brazilian research relating Honneth's RT with health; 3.2. Integrity and COIs: fundamental dilemmas and preventive strategies, and 3.3. Honneth's concepts validated in this research. Other topics refer to conclusions and bibliography.